Fostering creative English for specific purposes studies: implementation of flipped classroom method during COVID-19 pandemic at Antanas Gustaitis’ Aviation Institute, Vilnius Gediminas Technical University, Lithuania - Stunžaitė, Alisa; Skorupa, Pavel; Dubovičienė, Tatjana (Creativity Studies, 2024)
The global impact of the COVID-19 pandemic has had far-reaching consequences, including those within the realm of higher education. The flipped classroom method was adopted as an innovative teaching tool and creative approach within English for specific purposes classes at Vilnius Gediminas Technical University Antanas Gustaitis’ Aviation Institute to increase student motivation and enhance the teaching and learning process. The study’s results demonstrated that the flipped classroom method yielded both positive and negative outcomes, including more efficient mastery of learning material, improved planning of in-class and out-of-class activities, opportunities for additional research on covered topics, increased workload and time consumption, and other.